2023
DOI: 10.3748/wjg.v29.i22.3508
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of modified tetracycline dosing in a quadruple therapy for Helicobacter pylori: A retrospective single center study

Abstract: BACKGROUND Although highly effective as a component of Helicobacter pylori ( H. pylori ) treatment regimen, tetracycline is associated with a high incidence of medication-related adverse events. Modified dosing of tetracycline as part of quadruple therapy may improve safety while providing comparable eradication rates. AIM To evaluate the efficacy and safety of modified dosing of tetracycline in patients receiving te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(43 reference statements)
1
1
0
Order By: Relevance
“…to tetracycline include gastrointestinal symptoms, photosensitivity reactions, allergies, anaphylactic shock, asthma, and hemolytic anemia [21,22]. Loss of appetite, severe liver damage, and impaired tooth and bone growth have also been reported in prior studies [22]. This study showed a similar incidence of overall adverse events (28.57%) to previous studies, and the incidence of adverse events in the TET-T group was significantly lower than that in the TET-F group.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…to tetracycline include gastrointestinal symptoms, photosensitivity reactions, allergies, anaphylactic shock, asthma, and hemolytic anemia [21,22]. Loss of appetite, severe liver damage, and impaired tooth and bone growth have also been reported in prior studies [22]. This study showed a similar incidence of overall adverse events (28.57%) to previous studies, and the incidence of adverse events in the TET-T group was significantly lower than that in the TET-F group.…”
Section: Discussionsupporting
confidence: 78%
“…to tetracycline include gastrointestinal symptoms, photosensitivity reactions, allergies, anaphylactic shock, asthma, and hemolytic anemia [21,22]. Loss of appetite, severe liver damage, and impaired tooth and bone growth have also been reported in prior studies [22].…”
Section: Discussionmentioning
confidence: 92%